Vibration investigation of a quarter car with nonlinear shock absorber model - Ridhuan Siradj , Fadly Jashi Darsivan; Faris, Waleed Fekry (Trans Tech Publications, Switzerland, 2012)
The paper discusses the response and the accuracy of a quarter car model with a non-linear damping force. The non-linear shock absorber model was a result of an experiment that was conducted earlier and the mathematical model was verified. Based on this model simulation responses of the sprung and unsprung masses between a linear and the non-linear damper were compared. The wheel of the quarter car model was excited by a road profile and according to the results the non-linear quarter model showed responses which were not depicted and captured by the linear model.